2007
DOI: 10.1128/aem.00019-07
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Staphylococcus aureus Isolates from Buffalo, Bovine, Ovine, and Caprine Milk Samples Collected in Rio de Janeiro State, Brazil

Abstract: Eighty-four staphylococcal isolates were obtained from milk samples from cows, sheep, goats, and buffalo with subclinical mastitis and from colonization samples from ostriches. The animals were hosted in 18 small dairy herds and an ostrich breeding located in 10 municipalities of the state of Rio de Janeiro, Brazil. Thirty isolates were identified as Staphylococcus aureus by biochemical and molecular techniques and were comparatively characterized by phenotypic and genotypic methods. The molecular characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
92
3
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 33 publications
13
92
3
2
Order By: Relevance
“…The same fact is reported by Aires-de-Sousa et al (2007) comparing the sensitivity of Staphylococcus aureus isolates from bovine, goats and sheep.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The same fact is reported by Aires-de-Sousa et al (2007) comparing the sensitivity of Staphylococcus aureus isolates from bovine, goats and sheep.…”
Section: Discussionsupporting
confidence: 82%
“…isolates (7.1%). Although the antimicrobial resistance observed in the present study seems to be higher than those previously reported in Brazil and elsewhere (Aires-de-Sousa et al 2007, Kumar et al 2009), direct comparisons must be performed carefully since most investigations focused only on Staphylococcus aureus. Except for enroϐloxain and norϐloxacin, the present results indicate lower resistance rates to streptomycin, tetracycline and amoxicillin in Staphylococcus aureus as compared to CNS (Table 2).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Though the 88 S. aureus isolated between 2010 and 2012 belong to 14 different pulsotypes, 3 of them (A, B, D) group together 72 % and 5 of them (A, B, D, N, Z), 83 % of the isolates, confirming, like in other studies, that a restricted number of S. aureus clones are present within a herd or a farm (Hata et al 2006;Aires-de-Sousa et al 2007;Rabello et al 2007;Anderson et al 2012). Nevertheless, apart from the A and B pulsotypes (>90 % similarity), the other pulsotypes are not closely related and represent distinct lineages (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…No Brasil, os estudos com epidemiologia molecular, envolvendo S. aureus isolados de caprinos e ovinos ainda são escassos (Aires-de-Sousa et al 2007). Estes autores caracterizaram S. aureus isolados de casos de mastite subclínica nas espécies bovina, bubalina, caprina e ovina de diferentes municípios do estado do Rio de Janeiro.…”
Section: Mastite Em Pequenos Ruminantes: Etiologia E Epidemiologiaunclassified